Strategi Pengembangan SDM Melalui Pelatihan dan Pengembangan di Industri Manufaktur - Abdurrozzaq Hasibuan; Abrar Guntar Damanik; Rendy Purwanto; Zamy Anwar (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The manufacturing industry is one of the key sectors that plays an important role in a country's economy. In facing the challenges of globalization and technological advancement, human resource (HR) development through training and development becomes crucial. This study aims to analyze HR development strategies in the manufacturing sector and their impact on workforce competencies. The methodology used is literature review and secondary data analysis. The results show that well-planned training and development programs can improve workforce productivity and quality. In addition, companies need to implement strategies that focus on the specific needs of the industry and employees. The conclusion of this study emphasizes the importance of investing in training and development to enhance the competitiveness of the manufacturing industry.